Violence Culture by State and Peoples in Solving Indonesian Humanities Issues - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Violence become familiar to the Indonesian people, like a culture in solving every humanities and community issues. The state and community are become violence producer together. Even more reproducted for time by time, so that it sounds like Indonesia is violent country. This research is qualitative research with historical approach, case study, and empirical. Some cases that are usually become violence sources are agrarian conflict and ethnic conflict. In the historical view, the violence’s are friendly with our nation, both showed to the public or hidden conflict. Amoek, is our contribution through the science for explaining the condition where the violence as the manifestation from hidden character of Malayan that seems very friendly, polite, and full of smile. Violence at the local level can be solved through reconciliation between citizens or revitalization and re-actualization of local wisdom. However, against state violence against the people, what can be changed is the mindset of state administrators in managing conflict. This change will help a lot in reducing violence in Indonesia.Keywords: violence culture; amoek; local wisdom; structural violence;